Exploring links between Chinese military recruits' psychological stress and coping style from the person-environment fit perspective: The chain mediating effect of self-efficacy and social support - Wu, Chao; Hou, Guangdong; Lin, Yawei; Sa, Zhen; Yan, Jiaran; Zhang, Xinyan; Liang, Ying; Yang, Kejian; Zhang, Yuhai; Lang, Hongjuan (Frontiers in Psychology, 2022)
The choice of coping style of recruits under psychological stress in the process of military task execution has been an important topic in the promotion of military operations and cohesion of military forces. Taking a positive coping style under psychological stress can help recruits overcome the negative effects of stress and improve military morale and group combat effectiveness. Although soldiers' psychological stress in the process of military mission execution having an impact on coping style has been studied by a large body of literature, very little literature has focused on the mechanism of self-efficacy and social support between recruits’ psychological stress and coping style from the person-environment fit perspective. Therefore, this study was conducted to analyze the impact of recruits’ psychological stress on coping style through a chain mediation model and to discuss the role of self-efficacy and social support in this relationship. Two waves of survey data were utilized to test the research hypotheses on a sample of 1028 Chinese recruits performing military tasks. The results indicated that recruits’ psychological stress negatively impacted positive coping styles and positively correlated with negative ones. In addition, self-efficacy and social support mediated the relationship between psychological stress and positive coping style, and self-efficacy mediated the relationship between psychological stress and negative coping style. More importantly, self-efficacy and social support play the chain mediating effect between psychological stress and positive coping style.